2012
DOI: 10.1016/j.ajpath.2012.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

Keloid Disease Can Be Inhibited by Antagonizing Excessive mTOR Signaling With a Novel Dual TORC1/2 Inhibitor

Abstract: Keloid disease (KD) is a fibroproliferative lesion of unknown etiopathogenesis that possibly targets the PI3K/Akt/mTOR pathway. We investigated whether PI3K/Akt/mTOR inhibitor, Palomid 529 (P529), which targets both mammalian target of rapamycin complex 1 (mTORC-1) and mTORC-2 signaling, could exert anti-KD effects in a novel KD organ culture assay and in keloid fibroblasts (KF). Treatment of KF with P529 significantly (P < 0.05) inhibited cell spreading, attachment, proliferation, migration, and invasive prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 75 publications
5
61
0
Order By: Relevance
“…14, [17][18][19] Reduction in mTOR activity attenuates the progression of tubulointerstitial fibrosis in models of diabetic and polycystic kidney disease. 14,18) The evidences in carcinogenic models further suggest that increased mTOR signaling promotes loss of cadherins and increased fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14, [17][18][19] Reduction in mTOR activity attenuates the progression of tubulointerstitial fibrosis in models of diabetic and polycystic kidney disease. 14,18) The evidences in carcinogenic models further suggest that increased mTOR signaling promotes loss of cadherins and increased fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] It is thus evident that targeting reductions in mTOR activity attenuates the progression of tubulointerstitial fibrosis in models of diabetic and polycystic kidney disease. 14,[17][18][19] Conversely, increased mTOR signaling promotes loss of cadherins and increased fibrosis. 14,18,20) Likewise, rapamycin reduced fibrosis and attenuated disease progression in rat models of liver cirrhosis and pulmonary fibrosis.…”
Section: Curcumin Suppresses Epithelial-mesenchymal Transition Of Renmentioning
confidence: 99%
“…It has been shown that the active form of mTOR (phospho-mTOR) is overexpressed in keloid but not in normal skin [5,7,8]. Rapamycin and other mTOR inhibitors were shown to efficiently inhibit keloid keratinocytes [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The active form of mTOR (phospho-mTOR) is over-expressed in keloid [6,7]. At least two multiple-protein mTOR complexes exist, including the traditional mTOR complex 1 (mTORC1), and the more recently discovered mTOR complex 2 (mTORC2) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation